2023
DOI: 10.3390/pharmaceutics15082032
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of the Nose-to-Brain Delivery of PACAP for the Treatment of Neuronal Disease

Abstract: Research on the neuroprotective effect of pituitary adenylate cyclase-activating polypeptide (PACAP) and its use as a therapeutic agent has grown over the past 30 years. Both in vitro and in vivo experiments have shown that PACAP exerts a strong neuroprotective effect in many central and peripheral neuronal diseases. Various delivery routes have been employed from intravenous (IV) injections to intracerebroventricular (ICV) administration, leading either to systemic or topical delivery of the peptide. Over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…Many publications have suggested that some bioactive peptides with neuroprotective effects (e.g., PACAP) can exert a potential therapeutic role in the prevention and treatment of neurodegenerative diseases. PACAP (Table 1) was originally isolated from ovine hypothalamic extracts in view of its capacity to stimulate cyclic adenosine monophosphate formation in rat anterior pituitary cells [115]. Over the past three decades, PACAP has been shown to exert neurotrophic and neuroprotective effects in both in vitro and in vivo models of various neuropathologies [116].…”
Section: Such Peptides Can Be Applied In Treatment Approaches Against...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many publications have suggested that some bioactive peptides with neuroprotective effects (e.g., PACAP) can exert a potential therapeutic role in the prevention and treatment of neurodegenerative diseases. PACAP (Table 1) was originally isolated from ovine hypothalamic extracts in view of its capacity to stimulate cyclic adenosine monophosphate formation in rat anterior pituitary cells [115]. Over the past three decades, PACAP has been shown to exert neurotrophic and neuroprotective effects in both in vitro and in vivo models of various neuropathologies [116].…”
Section: Such Peptides Can Be Applied In Treatment Approaches Against...mentioning
confidence: 99%
“…The treatment of neuronal diseases presents a significant challenge owing to the BBB, which limits the delivery of most biomolecules in therapeutic quantities to the CNS. In addition to the challenge posed by the BBB, many neuroprotective agents, such as PACAP, have short half-lives [115]. Specifically, when PACAP is administered intravenously (IV), it exhibits a remarkably brief half-life of less than 5 min due to its rapid degradation by dipeptidylpeptidase IV (DPP IV) (an exopeptidase responsible for cleaving X-proline or While CPP-functionalized nanoparticles are still being investigated, there are obstacles for their widespread use in the treatment of NDs.…”
Section: Perspective Applications Of the Nose-to-brain Cpp-mediated D...mentioning
confidence: 99%
See 1 more Smart Citation